Growth trend and tolerance of Swingle citrumelo in Mazandaran calcareous soils, Iran - Ali Asadi Kangarshahi (University of Birjand, 2021)
Purpose: In this study, the response of Miyagawa Satsuma mandarin (Citrus unshiu) on Swingle citrumelo rootstock to calcareous soils of the east of Mazandaran in Iran was investigated. Research method: The experiment was done by seven soils with different calcium carbonate (2-45%) for two years. Findings: Soils with 14% total lime and 5% active lime had the highest shoot dry weight. Soils with 30 and 45% total lime, and 14 and 16% active lime had the highest chlorosis and soils with no lime or 3% active lime and 2 to 9% total lime had the least chlorosis. Soils with 2 and 9% total lime had the highest Fe concentration in root and the least chlorosis. Fe concentration in the roots was about 7.5 times that of the leaves, which show Fe accumulation and inactivation in the root. Mn concentration in leaves in most soils was lower than optimum, while available Mn in most soils was more than optimum (2.5 mg kg-1). Mn concentration at the roots was about 3.2 times of that in the leaves. In contrast, although available Zn of some soils was lower than optimum, in most soils the Zn concentration of leaves was in the optimum range. Research limitations: No limitations were founded. Originality/Value: Mn, due to low uptake and transmission efficiency from roots to shoots and severe deficiency in leaves is the most limiting microelement in this rootstock-scion combination. According to this research, Swingle citrumelo rootstock is appropriate in soils with total and active lime less than 14% and 5%, respectively.